2016
DOI: 10.1111/inr.12334
|View full text |Cite
|
Sign up to set email alerts
|

Iranian nursing students' perspectives on transition to professional identity: a qualitative study

Abstract: Educational policymakers can use our findings for developing strategies that facilitate and support nursing students' transition to professional identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Three studies were from Australia, [31][32][33] three from the United States, [34][35][36] one from Spain, 11 and two from the United Kingdom, with researchers from Australia. 8,19 There were also three studies from Iran, 18,37,38 two from Turkey, 39,40 and one each from Finland and Norway, 41 Japan, 42 Israel, 7 China, 43 and Canada. 44 Different data collection methods were used in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were from Australia, [31][32][33] three from the United States, [34][35][36] one from Spain, 11 and two from the United Kingdom, with researchers from Australia. 8,19 There were also three studies from Iran, 18,37,38 two from Turkey, 39,40 and one each from Finland and Norway, 41 Japan, 42 Israel, 7 China, 43 and Canada. 44 Different data collection methods were used in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that the majority of nurses have the necessary skills to take care of patients (Baillie 2011; Wilson & Hockenberry 2014;Oermann & Gaberson 2016). Other studies have demonstrated that the perceived image of nurses by the public is the same as portrayed in the media (Casella et al 2014;Heshmati Nabavi et al 2014;Neishabouri et al 2017;Averill & De Chesney 2015;Valizadeh et al 2014;Weaver et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests an inherent complexity in the area which makes it difficult for outsiders and newly trained professionals to assert their place in the profession. The change from student to graduate nurse has been examined by scholars such as Neishabouri et al (1) and Kaihlanen et al (2). While the shift to new nursing practices has been shown to demands support (3), and advancement to nurse practitioner to entail significant challenges (4), we found no studies on the progression from Registered Nurse (RN) to the more advanced ORN.…”
Section: Introductionmentioning
confidence: 99%